Analysis of vapor compression refrigeration cycle using advanced exergetic approach with Taguchi and ANOVA optimization and refrigerant selection with enviroeconomic concerns by TOPSIS analysis. (August 2022) - Ustaoglu, Abid; Kursuncu, Bilal; Metin Kaya, Alaattin; Caliskan, Hakan
Highlights: TOPSIS analysis was applied to decide the refrigerants with enviroeconomic concerns. Advanced exergy analysis along with Taguchi optimization was considered. R513a, R134a, and R448a were determined as the best refrigerants. Optimum parameters for high exergetic performance were calculated as A2 B3 C1 D3 E3 F1 . Compressor efficiency, evaporator were the most effective for avoidable destruction. Evaporator temperature was the most effective parameter on the performance. Abstract: In this study, TOPSIS analysis was applied to decide the optimum refrigerants with cost, safety, environmental and enviroeconomic concerns along with thermophysical properties. A vapor compression refrigeration cycle performance was investigated with the statistical and thermodynamic approaches. COP, exergy efficiency, total, avoidable, and unavoidable exergy destruction rates were calculated for various experimental designs. According to the relative proximity to the ideal solution, the best refrigerants for the system were determined as R513a, R134a, and R448a, respectively. The optimum parameters for the greatest COP and exergetic performance were calculated as A2 B3 C1 D3 E3 F1 . In the optimum case, the best COP and exergy efficiency of 2.65 and 10% and the lowest total exergy destruction of 0.34 kW were achieved for R134a. These are larger than all other 27 experimental patterns. The parameters having an impact on the COP, exergy efficiency, and total exergy destruction rate were found as T EVA  >  T CON  > Refrigerant >  η COM, H  >  η COM, L  >  P in (B > C > A > E > D > F). The evaporator temperature is the most effective parameter on the performance with about 42.8% for the performance. It is followed by that of condenser and refrigerant to be 32.5% and 13.8%. The most effective parameters for the avoidable exergy destruction rate were high- and low-pressure compressors efficiencies, evaporator temperature, and condenser temperature, respectively.